HOAX SEBAGAI BENTUK HUDUD MENURUT HUKUM ISLAM - Muhammad Arsad Nasution (Institut agama islam negeri Padangsidimpuan, 2017)
Hoax is one form of al-qazf which can be subjected to hudud punishment for the perpetrator that is 80 times volumes. Determination of hoax penalty with punishment jilid based qiyas khafi in terms of scholars Syafi'iyah, or istihsan in terms of scholars Hanafiyah. The illat that causes the analogy is the spread of false news that can harm others. Al-qazf contains false news about allegations of adultery to others, while hoaxes are also lying messages addressed by certain individuals who can harm others